If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 77 + -3x = 24x + 14 Reorder the terms: 77 + -3x = 14 + 24x Solving 77 + -3x = 14 + 24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24x' to each side of the equation. 77 + -3x + -24x = 14 + 24x + -24x Combine like terms: -3x + -24x = -27x 77 + -27x = 14 + 24x + -24x Combine like terms: 24x + -24x = 0 77 + -27x = 14 + 0 77 + -27x = 14 Add '-77' to each side of the equation. 77 + -77 + -27x = 14 + -77 Combine like terms: 77 + -77 = 0 0 + -27x = 14 + -77 -27x = 14 + -77 Combine like terms: 14 + -77 = -63 -27x = -63 Divide each side by '-27'. x = 2.333333333 Simplifying x = 2.333333333
| 5x+35=14x-36 | | 1+2[3(x-1)-5(2x-3)]=2x-7 | | 4x+5-10x=8+3x+12 | | 5x+31=tx+11 | | 4x^2+7x-8=0 | | 8b-4(b-2)=42 | | -6-20=-2n | | 2x+10=110-10x | | 8x+9=2x-13 | | 4x=8x+6 | | x+4+5+2=3+2+2x | | 2*(x+3)-3(x+1)=x-13 | | b(b+2)+4b^2=5b^2+9b+8 | | 10x-13=3x-7 | | y=2x^3-7x^2-15x | | x+11=8+x | | x+11=8+c | | n-9=7 | | n+27=44 | | a-4=3a-6 | | 5y-10=2y-3x+11 | | (11x)=(5x+30) | | 2x+8=8x-1 | | 51-81.623= | | 0=(.25x^4)-(2x^2)-1 | | 7.2g+1.5=6+3.2g | | 2x^2+4x-10=0 | | 5x+2(x-3)=12x-5+14 | | 4(2x+3)-6x=18 | | -8x-(3x+6)=44-x | | 2t(t+5)+1=3t-3-t^2 | | 4x+4+2x= |